PENGARUH TERAPI TOTOK PUNGGUNG TERHADAP TEKANAN DARAH, NYERI KEPALA, KUALITAS TIDUR, KADAR GLUKOSA DARAH DAN KOLESTEROL PADA LANSIA PENDERITA HIPERTENSI - Budiono Budiono; Sumirah Budi Pertami (Poltekkes Kemenkes Malang, 2022)
Hypertension in the elderly is often caused by a degenerative process in the arteries, the blood vessels become stiff so that peripheral resistance increases as a result of increased blood pressure/hypertension causing various problems in the elderly. Full-blooded back is one type of complementary therapy that is useful for blood circulation and provides a relaxing effect, by stimulating the release of endorphins, cortisol, this hormone can provide a calm/relaxing effect and vasodilation occurs in blood vessels resulting in a decrease in blood pressure. blood pressure, headaches, sleep quality, blood glucose and cholesterol levels in the elderly with hypertension. This research method is pre-experimental with one group pre-post test design. The sampling technique used accidental sampling with a sample size of 30. The results of the statistical analysis of the Wilcoxon sign rank test, obtained a p-value of 0.001 for blood pressure, headache, sleep quality and cholesterol levels (LDL), while for glucose levels p-value: 0.018 then H0 is rejected, meaning that there is an effect of full-blooded therapy on blood pressure, headaches, sleep quality, blood glucose and cholesterol (LDL) levels in elderly people with hypertension.